PROSES BERPIKIR KRITIS SISWA KELAS XI FARMASI SMK CITRA MEDIKA SRAGEN DALAM PEMECAHAN MASALAH MATEMATIKA - Retnowati, Dwi; Sujadi, Imam; Subanti, Sri (Jurnal Pembelajaran Matematika, 2016)
Abstract: The aims of this research was to describe the critical thinking process of the students in Grade XI pharmacy of SMK Citra Medika Sragen who have the high, moderate, and low abilities in each stage of clarification, analysis and solving strategy in solving mathematics problem. This research used qualitative case study approach. The results of research are the critical thinking process of the students as follows (1) The students with the high initial ability in mathematics: (a) clarification, they mention the information which they know and ask question by using their own language; (b) analysis, the students identify the necessary information. They formulate the step of problem solving and explain it confidently. It is proven when they illustrate the reason logically about the necessary information, using inequalities symbol, and non-negative condition. The students use their prior knowledge, after that, they draw a conclusion by returning the final result to the problem context; (c) solving strategy, they evaluate their work to re-calculate and that find another problem solving alternative at last; (2) The students the moderate initial ability in mathematics: (a) clarification, they mention the information which they know and ask question by using their own language;Â  (b) analysis, the students identify the necessary information to reread the problem. They formulate the solving problem step precisely. They use their prior knowledge to draw the conclusion by returning the final result to the problem context; (c) solving strategy, the students evaluate their work by seeing it; (3) The students with the low initial ability in mathematics: (a) clarification, they mention the information which they know and question it after reading it for few times and they need of question stimulus; (b) analysis, the students identify the necessary information to reread the problem, and, again, they need a question stimulus. They takes long time in formulating the problem solving. They draw the conclusion by returning the final result to the problem context; (c) solving strategy, the students commit the evaluation by seeing their work from the beginning to the end.Keywords: Critical Thinking Process, Mathematics Problem Solving, and Initial Ability in Mathematics.